The Accuracy English Verb Phrases Translation Into Indonesian By Using Google Translate - Laura Stephany Situmorang; Fenty Debora Napitupulu; Yessy Octaviana (Innovative: Journal Of Social Science Research, 2023)
The accuracy its very important when does translation activity, in this modern life many people using the Google Translate to help them translating a word, phrase, or a sentence, but sometimes it can be meaningless or not accurate. Therefore, the purpose of this study is to evaluate how accurately Google Translate has translated English verb tenses into Indonesian. This study used a qualitative method to reasearch the accuracy. The data's primary source was a translation that was produced by Google. The source of the data from the subtitles of The Boss Baby. There were numerous methods used to get the data, including: 1).Downloaded the Movie of The Boss Baby from the internet and, 2). The researcher selected 30 data of verb phrases from subtitle of The Boss Baby and make it in the table. To analyze the data, the techniques were : The raw data will be translated from Source Language (English) to Target Language (Indonesian) by Google Translate and then, The researcher analyzed the data by using Moorkens based on Nababan (2018:59), There were three types of translation: accurate, less accurate, and inaccurate. The results of this research showed that out of 30 pieces of data, 25 had accurate translations, 3 had less accurate translations, and 2 had inaccurate translations. The researcher reached the conclusion that Google Translate's translation of English verb tenses was correct.